JA:2021-15. Respiratory Exposures and Diseases among Agricultural Workers in the Central States Region of the United States. Issue 3 (2nd July 2020) - Johnson, Anthony; Rautiainen, Risto
ABSTRACT: Purpose : The Central States Center for Agricultural Safety and Health (CS-CASH) conducts surveillance to characterize occupational injury and illness frequencies, exposures, and preventive practices among farm and ranch operators in the central United States. This report focuses on respiratory diseases and associated exposures and preventive factors. Methods : The CS-CASH Farm and Ranch Health and Safety Survey was sent to randomly selected farmers and ranchers with an email address and farm sales exceeding 5000 per year; 22, 440 by email (online survey) and 16, 826 by mail (hardcopy form). The survey region consisted of Iowa, Kansas, Minnesota, Missouri, Nebraska, North Dakota, and South Dakota. Risk factors for respiratory disease (all combined, except chronic obstructive pulmonary disease) were evaluated using logistic regression. Results : A total of 3, 277 usable responses (response rate 19.47%) were received. The prevalence of respiratory diseases diagnosed by a physician were: asthma, 4.22%; farmer's lung, 2.22%; sinus disease (sinusitis), 4.75%; nasal inflammation/runny nose (rhinitis), 5.25%; and environmental allergies, 8.27%. The following exposures significantly increased the odds of having a respiratory disease: exposure to grain/feed/hay dust (Odds Ratio (OR): 2.15); animal confinement dust (OR: 1.57); road dust (OR: 2.03); manure and silage gasses (OR: 1.64), anhydrous ammonia (OR: 1.47); fuels/solvents/paints (OR: 1.82); having cow/calf operation (OR: 1.26); growing wheat (OR: 1.28); and growing canola (OR: 1.70). Practical Application : These findings demonstrate the need for effective methods to control dust and gas exposures to reduce the risk of respiratory diseases among farmers and ranchers.